Leadership in a Globalized World complexity, dynamics and risks - Leautier, Frannie (London Palgrave Macmillan, 2014)
This book investigates key issues facing leaders in increasingly complex decision-making environments as a result of globalization. It presents a synthesis and interpretation of academic research in multiple disciplines and integrates it into a practical approach that is readily useable by leaders in government, corporations, and civil society.
Includes index and bibliograhy
Keywords: Leadership